Application Of Innovation In Marketing Strategies For Sustainable Tourism In Raja Ampat - Astuti, Ni Luh Gde Sari Dewi; Sunny, Milla Permata; Suharyati, Suharyati; Nasfi, Nasfi; Sofyan, Hady (LPPM Universitas PGRI Sumatera Barat, 2025)
Raja Ampat, located in Southwest Papua, Indonesia, is known as a paradise for divers and nature lovers with its extraordinary underwater and land natural beauty. This archipelago consists of more than 1,500 small islands surrounded by four main islands: Misool, Salawati, Batanta, and Waigeo. As part of the Coral Triangle, Raja Ampat is a center of marine biodiversity with hundreds of unique and endangered species. The name